Therapeutic Potential of Clove Oil in Mitigating Cadmium-Induced Hepatorenal Toxicity Through Antioxidant, Anti-Inflammatory, and Antiapoptotic Mechanisms - Inas M. Elgharib; Fatma M. Abdelhamid; Gehad E. Elshopakey; Hatem Sembawa; Talat A. Albukhari; Waheed A. Filimban; Rehab M. Bagadood; Mohamed E. El-Boshy; Engy F. Risha (Pharmaceuticals)
Hazardous heavy metals, particularly cadmium (Cd), are widely distributed in the environment and cause oxidative stress in various animal and human organs. Clove oil (CLO), a common aromatic spice, has been used as a traditional medication as it has potent anti-inflammatory, antioxidant, and hepatoprotective properties. Background/Objectives: This study aimed to investigate the antioxidant, antiapoptotic, and anti-inflammatory effects of clove oil (CLO) against hepatorenal toxicity induced by cadmium (Cd). Methods: Twenty rats were equally divided into four groups: a control group, a Cd group treated with 15 mg/kg b.wt CdCl2, a CLO group administered 200 mg/kg b.wt CLO, and a Cd+CLO group. All groups were orally treated for 4 weeks. Results: Cadmium (Cd) exposure caused anemia and hepatorenal damage, as evidenced by increased serum levels of urea, creatinine, uric acid, total bilirubin (including its direct and indirect fractions), and elevated activities of liver enzymes such as alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP). However, total protein and albumin levels decreased. Furthermore, there was a decrease in the levels of glutathione, glutathione transferase, and catalase in the liver antioxidant profiles. Meanwhile, malondialdehyde levels increased. Cadmium toxicity caused elevated expression of liver apoptosis markers, such as tumor necrosis factor-alpha (TNF-α) and caspase-3, and inflammation. CLO ameliorated the oxidative effects of Cd through decreasing urea (27.4%), creatinine (41.6%), liver enzymes, and hepatic apoptotic markers while increasing levels of total protein, albumin, and hepatic values of SOD (60.37%), CAT (64.49%), GSH (50.41%), and GST (9.16%). Conclusions: Hematological and biochemical parameters, as well as the antioxidant system, improved following clove oil treatment, leading to a reduction in hepatorenal damage. Therefore, it is possible to conclude that CLO protects rats from inflammation, apoptosis, and hepatorenal oxidative damage caused by Cd poisoning. Comprehensive translational research is required to validate CLO’s efficacy and safety of use in humans. Future studies should focus on elucidating the precise molecular mechanisms, optimal dosing strategies, and potential synergistic effects of CLO with other therapeutic agents.